Identify Infrastructure Availability in Parit Tokaya Village South Pontianak District Pontianak City, West Kalimantan - Weni Dewi Utami (Syntax Corporation Indonesia, 2023)
This study aims to identify the availability of infrastructure in Tokaya Parit Village, South Pontianak Regency, Pontianak City, West Kalimantan. The method used in this study is a survey with data collection techniques through direct interviews with local communities and direct observation in the field. The results showed that the availability of infrastructure in Tokaya Parit Village is still inadequate, especially in terms of roads, clean water, and sanitation. Most of the roads in Tokaya Parit Village are still unpaved dirt roads and are badly damaged during the rainy season. The source of clean water available in this village is also still very limited, so people often have to take water from rivers or wells that do not meet health standards. In addition, sanitation in this village is also still inadequate, with most people still using squat-style toilets or mobile latrines. In conclusion, this study shows that the availability of infrastructure in Tokaya Parit Village still needs to be improved in order to meet the needs of the local community. There needs to be attention and support from related parties, both government and private, to increase the availability of infrastructure in this village, so that people can live properly and meet their basic needs